Recuperação de platina de resíduos contendo tifenilfosfina, trifenilarsina e trifenilestibina - Barbiéri, Roberto Santos; Rocha, Júlio Cesar; Massabni, Antonio Carlos; Belatto, Carlos Roberto (Eclética Química, 1988)
.